Peran Teknologi Dalam Pembelajaran Daring Pendidikan Agama Islam Di Masa Pandemi Covid-19 - Rosniati, Nia; Rinanda Achirani Dewi; Ardhya Garini Yasmin Mulyana; Cici Isnawati; Hisny Fajrussalam (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Online learning is a challenge for educators and students during the COVID19 pandemic. In addition, this pandemic has had several impacts on the sustainability of the education process. One of the impacts felt by the world of education due to the COVID-19 pandemic, namely the existence of policies from the government related to changes in the learning system which was originally offline or turned into online learning (online). Therefore, technology plays an important role in supporting online learning in order to improve the quality of education, including in the implementation of Islamic Religious Education learning during the COVID-19 pandemic. The purpose of this research is to find out how the role of technology in online learning of Islamic Religious Education. This research is qualitative research with a descriptive approach and uses a literature review data collection method, through journal articles that are relevant to this research. The results of the study show that technology does play an important role in online PAI learning during the COVID-19 pandemic, by utilizing technology through supporting platforms, such as the Whatsapp platform, zoom, and others.